Report of the Finance Committee - Hinshaw, C. Elton (American Economic Review, 2000)
The Finance Committee of the American Economic Association met at the Chicago Club, Chicago, IL, at 12:30 P.M. on December 9, 1998. Present were John Cochrane, Robert Dederick, Robert Hamada, C. Elton Hinshaw (Chair) , and John Siegfried (Secretary of the Association ) ; Representing Stein Roe & Farnham, investment counsel for the Association, were Robert McNeill, Scott W. Vogg, and Debbie Jansen. In 1987, the Committee reviewed recommendations presented by the AEA Committee on indexing Association funds concerning the long-term allocation of the Association’s investment assets. As a result of that recommendation, it was agreed that the Association’s portfolio comprise a combination of an S&P 500 Index Fund, Stein Roe & Farnham’s specialty equity mutual funds, and a bond portion managed by Stein Roe & Farnham. This restructuring took place at the end of June 1988. The current portfolio includes holdings in the Vanguard Index Trust Fund, as well as several special Growth Funds and an International Fund, under the supervision of Stein Roe & Farnham (SRF) . The Fixed Income portion of the portfolio is currently invested in SRF’s Intermediate Term Government and Corporate taxable funds. With respect to the calendar-year 1998 performance of the Association’s portfolio, the total return including cash, bonds, and equity holdings was approximately 17.2 percent. The benchmark, which consisted of 5 percent cash, 25 percent Lehman G/C Intermediate Bond Index, 60 percent S&P 500 Index, and 10 percent EAFE index returned 16.7 percent. The returns from the AEA portfolio have now outperformed the benchmark portfolio for six years in a row. The Committee discussed a change to the allocation of the portfolio and the benchmark. It was approved that the benchmark portfolio would become 0 percent cash, 25 percent Lehman G/C Intermediate Bond Index, 60 percent S&P 500 index, 5 percent Russell 2000 index, and 10 percent EAFE index. Additionally, it was agreed to move 5 percent of the assets in the S&P 500 Index Fund into the bond portion of the portfolio immediately. Members can obtain a list of the assets in the portfolio by writing the Treasurer.